2022
DOI: 10.7554/elife.72657
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sequence phylogenetics to quantify patterns of HIV transmission in the context of a universal testing and treatment trial – BCPP/Ya Tsie trial

Abstract: Background: Mathematical models predict that community-wide access to HIV testing-and-treatment can rapidly and substantially reduce new HIV infections. Yet several large universal test-and-treat HIV prevention trials in high-prevalence epidemics demonstrated variable reduction in population-level incidence.Methods: To elucidate patterns of HIV spread in universal test-and-treat trials we quantified the contribution of geographic-location, gender, age and randomized-HIV-intervention to HIV transmissions in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
(63 reference statements)
2
19
0
Order By: Relevance
“…Empiric incidence data published over the last decade documents widespread declining incidence across the African continent 24 , and UNAIDS mathematic models from eastern and southern Africa have estimated a 43% reduction in incidence regionally since 2010 1 . Our findings are also compatible with genderstratified HIV incidence data from prospective African population-level studies that indicate greater differences in rates of new infections between men and women in the same cohort over calendar time 24 , data from population surveillance studies and HIV treatment and prevention trials showing lower levels of viral suppression among men compared to women with HIV 64,65 , and phylogenetic studies from Botswana 28 and Zambia 29 . Together, these observations suggest that the principal characteristics of the evolving HIV epidemic summarized in Table 1 likely apply more broadly in similar rural and semi-urban populations across Eastern and Southern Africa.…”
Section: Discussionsupporting
confidence: 86%
“…Empiric incidence data published over the last decade documents widespread declining incidence across the African continent 24 , and UNAIDS mathematic models from eastern and southern Africa have estimated a 43% reduction in incidence regionally since 2010 1 . Our findings are also compatible with genderstratified HIV incidence data from prospective African population-level studies that indicate greater differences in rates of new infections between men and women in the same cohort over calendar time 24 , data from population surveillance studies and HIV treatment and prevention trials showing lower levels of viral suppression among men compared to women with HIV 64,65 , and phylogenetic studies from Botswana 28 and Zambia 29 . Together, these observations suggest that the principal characteristics of the evolving HIV epidemic summarized in Table 1 likely apply more broadly in similar rural and semi-urban populations across Eastern and Southern Africa.…”
Section: Discussionsupporting
confidence: 86%
“…Botswana has recently achieved the 95-95-95 targets that UNAIDS specified needed to be reached by 2030 in order to eliminate HIV: 95% of people living with HIV to be diagnosed, 95% of the diagnosed to be on treatment, and 95% of those on treatment to be virally suppressed (Mine et al, 2022). However, transmission is continuing (Magosi et al, 2022), as is urbanization and large-scale population movements (Okano et al, 2021). The same processes that we have identified that may have contributed to the development of the generalized hyper-endemic HIV epidemic in Botswana may prevent the elimination of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal is known about the epidemiology of HIV in Botswana in terms of the increase in prevalence and geographic variation in prevalence (Magosi et al, 2022; Novitsky et al, 2015; Novitsky et al, 2020; Okano et al, 2021). The first case of AIDS was reported in 1985 from the nickel mining town of Selebi Phikwe (African Natural Resources Center, 2016); in the late 1980s, additional cases were reported from two diamond mining towns (Jwaneng and Orapa) and the city, Francistown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pybus summarized insights into the SARS-CoV-2 pandemic and other outbreaks from large scale phylogenetic analysis [ 18 ]; and Emma Hodcroft presented the CoVariants dashboard, which allows interactive exploration of SARS-COV-2 variants of concern. Finally, Christophe Fraser spoke about harnessing within- and between-host pathogen population genetics, using the approach implemented in P hyloscanner [ 19 ], to gain insights into the epidemiology, evolution and pathogenicity of diverse pathogens ranging from methicillin resistant Staphylococcus aureus (MRSA) [ 20 ] to SARS-COV-2 and HIV [ 21 ].…”
Section: Other Topics Coveredmentioning
confidence: 99%